Functionalized KIT-6/polysulfone mixed matrix membranes for enhanced CO2 /CH4 gas separation - Chew, T.L. (MDPI AG, 2020)
The development of mixed matrix membranes (MMMs) for effective gas separation has been gaining popularity in recent years. The current study aimed at the fabrication of MMMs incorporated with various loadings (0â4 wt) of functionalized KIT-6 (NH2 KIT-6) KIT: Korea Advanced Institute of Science and Technology for enhanced gas permeation and separation performance. NH2 KIT-6 was characterized by field emission scanning electron microscope (FESEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and N2 adsorptionâdesorption analysis. The fabricated membranes were subjected to FESEM and FTIR analyses. The effect of NH2 KIT-6 loading on the CO2 permeability and ideal CO2 /CH4 selectivity of the fabricated membranes were investigated in gas permeation and separation studies. The successfulness of (3-Aminopropyl) triethoxysilane (APTES) functionalization on KIT-6 was confirmed by FTIR analysis. As observed from FESEM images, MMMs with no voids in the matrix were successfully fabricated at a low NH2 KIT-6 loading of 0 to 2 wt%. The CO2 permeability and ideal CO2 /CH4 selectivity increased when NH2 KIT-6 loading was increased from 0 to 2 wt%. However, a further increase in NH2 KIT-6 loading beyond 2 wt% led to a drop in ideal CO2 /CH4 selectivity. In the current study, a significant increase of about 47% in ideal CO2 /CH4 selectivity was achieved by incorporating optimum 2 wt% NH2 KIT-6 into the MMMs. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.